"The Red Lady of El Mirón". Lower Magdalenian life and death in Oldest Dryas Cantabrian Spain: an overview. (August 2015) - Straus, Lawrence G.; González Morales, Manuel R.; Carretero, Jose Miguel; Marín-Arroyo, Ana Belen
Abstract: This synthesis article summarizes the multidisciplinary evidence and interpretations of the first substantial human burial of Magdalenian age to be discovered on the Iberian Peninsula. A robust, relatively tall, apparently healthy, probably female adult was buried at the rear of the living area in El Mirón Cave in the Cantabrian Cordillera of Spain about 18, 700 calendar years ago. She had lived in the cold, open environment of Oldest Dryas, with a subsistence based on hunting mainly ibex and red deer, fishing salmon and some gathering of plants, including some starchy seeds and mushrooms. The technology of her group included the manufacture and use of stone tools and weapon elements made on both excellent-quality non-local flint and local non-flints, as well as antler projectile tips and bone needles. Her burial may have been marked by rock engravings suggestive of a female personage, by red ochre staining of a large block adjacent to her skeleton, and by engravings on the adjacent cave wall, and the burial layer itself was intensely stained with red ochre rich in specular hematite specially obtained from an apparently non-local source. The ochre may constitute the only demonstrable "grave offering". The grave was partially disturbed by a carnivore of wolf size after the corpse had decomposed. Then, it is hypothesized that the skeleton was covered over again and (re-) stained by humans after they (or the carnivore) had removed the cranium and most of the large long bones. Highlights: First human burial of Magdalenian age found in Iberia, dated stratigraphically & by C14. A ritualized, reworked burial marked with rock art and red ochre. Skeleton is of a robust adult woman in good health, associated with artifacts, but no obvious grave goods. Associated with rich Lower Magdalenian lithic and osseous artifact assemblages. Diet dominated by ungulate meat (ibex and red deer) and fish (salmon), but with some plant foods (mushrooms, fungi and seeds).